Lithium ion battery performance of micro and nano-size V2O5 cathode materials. (2022) - Jayalakshmi, T.; Harini, R.; Nagaraju, G.
Graphical abstract: Highlights: The preparation of micro-size vanadium oxide (V2 O5 ) material by foaming process and the preparation of V2 O5 nanoparticles by combustion method. Both the presented methods are facile methods. Characterization of prepared materials by XRD, FTIR, BET analysis and TEM & SEM analysis. And mainly studied the rechargeable lithium ion battery performance of micro & nano size V2 O5 as cathode materials at 1.5–4.0 V. The nano-size V2 O5 shows the high capacity (290 mAh g −1 ) compared to micro-size V2 O5 (240 mAh g −1 ) for 100 cycles. The battery results demonstrate V2 O5 NPs shows good cyclability performance and better capacity retention than the micro-size V2 O5 . The good performance of V2 O5 NPs could attribute to the mesoporous nature and easy penetration due to shorting of Li ion diffusion. This indicates that V2 O5 NPs fabricated by this method proven to be one of the good cathode material for LIB for future applications. Abstract: A comparison study of the Li-ion battery performance of micro and nano-size V2 O5 has been carried out. The micro-size V2 O5 has been prepared at room temperature, and the nano-size V2 O5 has been prepared by the combustion method. For characterization of the prepared materials, X-ray diffraction (XRD), FTIR, Brunauer-Emmett-Teller (BET) surface area, and transmission electron microscopy have been employed. The nano-size V2 O5 exhibits 290 mAh g −1 (98% of theoretical capacity), whereas the micro-sized V2 O5 exhibits 240 mAh g −1 specific discharge capacity at a C/10 current rate of 1.5–4.0 V. Nano-size V2 O5 exhibited reasonable discharge capacities at different C-rates (discharge rate of current) and delivered better cycliability of about 100 charge discharge cycles compared to micro-size V2 O5 . This report reveals that reduced particle size with the good porous nature of nano-size V2 O5 leads to better enhancement of lithium ion battery performance.